2018
DOI: 10.1007/s11886-018-1004-9
|View full text |Cite
|
Sign up to set email alerts
|

HDL Mimetics Infusion and Regression of Atherosclerosis: Is It Still Considered a Valid Therapeutic Option?

Abstract: Purpose of ReviewThis review aims to summarize and discuss the recent findings in the field of using HDL mimetics for the treatment of patients with coronary artery disease.Recent FindingsFollowing the largely disappointing results with the cholesteryl ester transfer protein inhibitors, focus moved to HDL functionality rather than absolute HDL cholesterol values. A number of HDL/apoA-I mimicking molecules were developed, aiming to enhance reverse cholesterol transport that has been associated with an atheropro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 49 publications
2
31
1
1
Order By: Relevance
“…Preliminary studies showed CER‐100 can rapidly mobilise large amounts of cholesterol into the HDL fraction. However, once again larger safety and efficacy trials did not observe any differences in atheroma regression in the CER‐100 group …”
Section: Pipeline Therapiesmentioning
confidence: 88%
See 4 more Smart Citations
“…Preliminary studies showed CER‐100 can rapidly mobilise large amounts of cholesterol into the HDL fraction. However, once again larger safety and efficacy trials did not observe any differences in atheroma regression in the CER‐100 group …”
Section: Pipeline Therapiesmentioning
confidence: 88%
“…This has led to a shift in focus towards the functional properties of HDL (particularly its role in reverse cholesterol transport) rather than raising HDL levels. There are three main steps to reverse cholesterol transport: (i) cholesterol efflux, where HDL/apolipoprotein A‐1 (apoA‐1) remove excess cholesterol from cells; (ii) lipoprotein remodelling, where HDL undergoes structural modifications; and (iii) hepatic lipid intake, where HDL releases cholesterol to the liver for final excretion . Several HDL mimetics have been tested in humans.…”
Section: Pipeline Therapiesmentioning
confidence: 99%
See 3 more Smart Citations